ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN DIVIDEN, DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Mochamad Indra Saputra; Fina Fitriyana (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research aims to determine and empirically test the influence managerial ownership, dividend policy, and debt-to-value policy company with empirical studies on mining sector companies listed on the Indonesian Stock Exchange in 2019-2022. This type of research is associative quantitative research. Population in this study using 83 companies. Sampling method in this research used a purposive sampling method to produce a sample A total of 13 companies were included in the research sample. Deep data This research uses secondary data taken from annual reports companies with 52 observation data. For data analysis techniques used is panel data regression analysis. Data processing in research using the help of eviews 10 software. The research results show that Managerial ownership has no effect on company value. Policy dividends have no effect on company value. And debt policy influence on company value. But simultaneously ownership managerial, dividend policy, and debt policy influence value company.